Noon : simple recipes for scrumptious midday meals and more - Peters, Meike (Food writer and Photographer) (Chronicle Books, 2023)
"This bold new cookbook by James Beard Award-winning author and photographer Meike Peters invites us to indulge in simple, satisfying, and scrumptious meals to feed our midday cravings. With a few tricks and clever flavor combinations to keep your mind, body, and soul happy, Noon makes it easy to treat yourself throughout the day"--